THE ROLE OF NURSING IN PROMOTING CARDIOVASCULAR HEALTH AND PREVENTING HEART DISEASE - Khalid Yahya Daraaj, Nisrin Hamzah M Alkhaibari, Talal Khlef Alenzi, Nouf Khatem Almutairi, Ghadah Abdullah Alanizi, Hajar Mesfer Almutairi, Meshari Saad Alsuwailem, Hendamh Ali Maoodah, ‏Bader Ali Jehni, ,; Ahmad Majed Sarhed Almotery, Maha Dham Alshammar, Al Homedi Khalid Alshammari, (Chelonian Research Foundation, 2022)
Inadequate self-care practices may result in a heightened likelihood of negative health consequences in those suffering from heart failure. Despite several research on the efficacy of nurse-led self-care teaching, there is still uncertainty surrounding the impact of nurse-led treatment in heart failure. The objective of this research was to assess the evidence on the efficacy of nurse-led cardiovascular self-care education in improving health outcomes among patients with coronary artery disease. In order to identify studies that examined the effectiveness of nurse-led education in enhancing self-care among heart failure patients, a thorough search was conducted between January 2000 and October 2019. This search involved systematically searching six electronic records: CINAHL, PubMed, Cochrane library, Embase, SCOPUS, and Web of Science. The research data pieces that satisfied the criteria were evaluated and analyzed separately utilizing random-effects meta-analysis techniques. Out of a total of 612 research, only eight papers met the criteria to be included in this study. Nevertheless, the provision of heart failure self-care instruction by nurses did not result in any enhancements in the quality of life or heart failure knowledge. Research on the efficacy of nurse-led coronary artery disease self-care education mostly focuses on the favorable impact on patients' health outcomes, while there is currently minimal information about the efficacy of the nurse-led method. Thus, it is essential to conduct rigorous randomized controlled trials that provide comprehensive and precise descriptions of the intervention components. Keywords: heart failure, self-care, nursing, systematic reviews, meta-analysis